Modern treatment of endometrial local hyperplastic processes from positions of the pathogenic approach - Benyuk, V. O.; Kravchenko, Y. V.; Kovaliuk, T. V.; Beniuk, S. V.; Usevych, I. A. (Reproduktivnaâ èndokrinologiâ, 2020)
Purpose of research: to improve the treatment effectiveness of patients with endometrial local hyperplasia by use of endoscopic technologies and pathogenetical postoperative therapy.Materials and methods. 66 women whose treatment algorithm included 4 stages (hysteroscopic polyp ablation followed by the morphological study, hormonal therapy aimed at the endometrium suppression, hormonal status optimization and dispensary observation within 5 years) were the subject of the study. After complex examination and histological verification of endometrial polyposis diagnosis patients were divided into two groups: A (n = 34) with the immune corrective therapy and B (n = 32). Examination algorithm included the endometrial immune histochemical examination with its immune histochemical profile definition.Study results. Histological screening of endometrium state resulted that 9 (26.5%) patients in the A group had the chronic endometritis features. The corresponding index for the B group stood for 15 patients (46.9%) that is 20.4% higher compared to the A group. Estrogen receptors expression with the background of progestogen treatment indicated the 1.2 times lowering for both groups. The viral and bacterial complex screening indicated the endometrial pathogenic contamination dramatic decrease. Study of tumor necrosis factor’s level determined the straightforward tendency with the CD 138 index dynamics. In a year term the complete treatment effect in A group was observed among 29 patients (85.2%), and the endometrial polyposis recurrence was observed among 5 (14.8%) patients.Conclusions. It is necessary to take into account the woman’s age, joint genital and somatic pathology’s presence and the immune histochemical profile of hyperplastic endometrial while determining the endometrial pathology differentiated treatment tactics. Additional immune corrective therapy with the antibacterial treatment determines the receptor phenotype restoration, normalization of tumor necrosis factor-α lever and increases the endometrial polyposis treatment effectiveness up to 22.7%. Цель исследования: повышение эффективности лечения больных с локальной гиперплазией эндометрия путем применения эндоскопических технологий и патогенетически обоснованной послеоперационной терапии.Материалы и методы. В исследование вошли 66 женщин, алгоритм лечения которых состоял из 4 этапов: гистероскопическое удаление полипа и измененного эндометрия с последующим морфологическим исследованием, гормональная терапия, направленная на супрессию эндометрия, оптимизация гормонального статуса, диспансерное наблюдение в течение 5 лет. После комплексного обследования и гистологической верификации диагноза больные с полипозом эндометрия были разделены на две группы: группа А (n = 34), которая дополнительно получала иммунокорригирующую терапию, и группа В (n = 32). Алгоритм обследования включал иммуногистохимическое исследование эндометрия с определением его иммуногистохимического профиля.Результаты исследования. Гистологический скрининг состояния эндометрия показал, что у 9 (26,5%) больных группы А наблюдались признаки хронического эндометрита. В группе В этот показатель составил 15 (46,9%), что на 20,4% больше, чем в группе А. Уровень экспрессии эстрогеновых рецепторов на фоне лечения прогестинами показал снижение в 1,2 раза в обеих группах. Проведение комплексного вирусно-бактериального скрининга выявило резкое уменьшение количества патогенов контаминации эндометрия. Исследование уровня фактора некроза опухоли в смывах из полости матки указало на однонаправленную тенденцию с динамикой показателя CD 138. Полный эффект лечения в группе А определен через год у 29 (85,2%) больных, у 5 (14,8%) женщин наблюдали рецидив полипоза эндометрия.Выводы. Определяя тактику дифференцированного лечения патологии эндометрия, необходимо учитывать возраст женщины, наличие сочетанной генитальной и сопутствующей соматической патологии, данные иммуногистохимического профиля гиперплазированного эндометрия. Дополнение антибактериального лечения иммунокорригирующей терапией содействует восстановлению рецепторного фенотипа, нормализации уровня фактора некроза опухоли, увеличивает на 22,7% эффективность лечения локальной гиперплазии эндометрия (полипов эндометрия). Мета дослідження: підвищення ефективності лікування хворих з локальною гіперплазією ендометрія шляхом застосування ендоскопічних технологій та патогенетично обґрунтованої післяопераційної терапії.Матеріали і методи. У дослідження включили 66 жінок, алгоритм лікування яких складався з 4 етапів: гістероскопічне видалення поліпа і зміненого ендометрія з подальшим морфологічним дослідженням, гормональна терапія, спрямована на супресію ендометрія, оптимізація гормонального статусу, диспансерне спостереження протягом 5 років. Після комплексного обстеження і гістологічної верифікації діагнозу хворі з поліпозом ендометрія були розділені на дві групи: група А (n = 34), яка додатково отримувала імунокоригуючу терапію, і група В (n = 32). Алгоритм обстеження включав імуногістохімічне дослідження ендометрія з визначенням його імуногістохімічного профілю.Результати дослідження. Гістологічний скринінг стану ендометрія показав, що у 9 (26,5%) хворих групи А спостерігалися ознаки хронічного ендометриту. У групі В цей показник склав 15 (46,9%), що на 20,4% більше, ніж у групі А. Рівень експресії естрогенових рецепторів на фоні лікування прогестинами показав зниження в 1,2 разу в обох групах. Проведення комплексного вірусно-бактеріального скринінгу показало різке зменшення кількості патогенів контамінації ендометрія. Дослідження рівня фактора некрозу пухлини в змивах з порожнини матки засвідчило односпрямовану тенденцію з динамікою показника CD 138. Повний ефект лікування в групі А визначено через рік у 29 (85,2%) хворих, у 5 (14,8%) жінок спостерігали рецидив поліпозу ендометрія.Висновки. Визначаючи тактику диференційованого лікування патології ендометрія, необхідно враховувати вік жінки, наявність поєднаної генітальної і супутньої соматичної патології, дані імуногістохімічного профілю гіперплазованого ендометрія. Доповнення антибактеріального лікування імунокоригуючою терапією сприяє відновленню рецепторного фенотипу, нормалізації рівня фактору некрозу пухлин, збільшує на 22,7% ефективність лікування локальної гіперплазії ендометрія (поліпів ендометрія).